(untitled) (OODBODHAN, 2026)
Islanded DC microgrid are an efficient and reliable way to integrate renewable energy sources in standalone and remote power systems. In comparison with AC microgrid, DC architectures reduce the stages of power conversion and improve efficiency, as well as simplify the control; however, how to maintain stable operation under variable renewable generation is yet a big challenge. This paper is concerned with the modeling and centralized control of an islanded DC microgrid that consists of solar photovoltaic, wind energy, and battery energy storage systems using MATLAB/Simulink. This paper discuss a centralized control approach, which regulates the DC bus voltage and coordinates the power flow among renewable sources and batteries through global system measurements. Simulation studies are carried out under dynamic operating conditions of change in solar irradiance, wind speed, and load demand. The results obtained show that under the proposed control strategy, the DC bus voltage remains within ±2% of its reference value at all instances of the operating period. The photovoltaic power is between 7-10 kW, whereas the wind power increases up to 8-9 kW under transient conditions. The battery compensates for the net power imbalance and, hence, smoothly switches between discharging and charging modes while keeping the state of charge within a safe window of 40-80%. These results confirm that centralized control provides effective voltage regulation, robust power management, and stability operation of islanded DC microgrid with hybrid renewable energy sources.